Laptops and learning spaces: Online, offline and in between - Brown, Cheryl; Pallitt, Nicola (Proceedings of the International Conference on Networked Learning, 2014)
Researchers in the field of networked learning have recently sought to understand the sociomaterial practices involved in networked learning (McConnell et al., 2012). This paper investigates the sociomaterial influence of laptops as students traverse a variety of learning spaces and considers the role of these devices in changing learning. Current conceptions of learning spaces in Higher Education prioritise physical ‘places’ such as libraries and lecture theatres. The mobility of laptops and related technologies challenge this perception. This paper brings together some central ideas for understanding learning spaces (Boys, 2011; Temple, 2011; Savin-Baden, 2008) and positions these in relation to networked learning. We consider the interrelationship between physical learning places and immaterial, technologically mediated spaces. The paper reports on data from a one-to-one laptop pilot at the University of Cape Town, South Africa. While the initial project was conceptualised as an evaluation of students' laptop use in four courses, the pilot evolved according to the needs of the project and became more akin to participatory action research over time. We consider dynamics related to networked learning in a resource constrained higher education environment, where personal computer access and internet connectivity is not the norm. In our context, many students rely on mobile phones as their primary means of internet access off campus (Czerniewicz, Williams & Brown, 2009). Students’ laptop use suggests that learning spaces cross boundaries between formal and informal learning, include a range of physical settings, and involve learning both online, offline and in between. Our analytic focus has shifted from separate contexts or bounded spaces to a continua of activities across domains. This paper contributes to previous research on reconceptualising learning space in networked learning (Smith, 2012) and concurs with Ryberg & Larsen (2008) that we are seeing increased opportunities for individualised as well as connected learning. As a mobile device, the laptop facilitates interactions, challenges traditional learning spaces and influences educational practice. We argue that the notion of learning spaces allows researchers to attend to the nuances of teaching and learning interactions with technologies in a variety of physical places. In relation to laptop use at university, networked learning involves the orchestration and personal management of learning spaces online, offline and in between which depends on students' discipline-specific needs.